2023
DOI: 10.1038/s41392-023-01354-2
|View full text |Cite
|
Sign up to set email alerts
|

OTUB1 promotes osteoblastic bone formation through stabilizing FGFR2

Abstract: Bone homeostasis is maintained by the balance between osteoblastic bone formation and osteoclastic bone resorption. Dysregulation of this process leads to multiple diseases, including osteoporosis. However, the underlying molecular mechanisms are not fully understood. Here, we show that the global and conditional osteoblast knockout of a deubiquitinase Otub1 result in low bone mass and poor bone strength due to defects in osteogenic differentiation and mineralization. Mechanistically, the stability of FGFR2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In addition, the intracellular stability of FGFR2 is maintained by OTUB1, which inhibits FGFR2 ubiquitination to avoid its fate of lysosome degradation. Osteoblast conditional Otub1 knockout mice showed a bone loss, suggesting an important role of Fgfr2 in maintaining bone homeostasis ( Zhu et al, 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intracellular stability of FGFR2 is maintained by OTUB1, which inhibits FGFR2 ubiquitination to avoid its fate of lysosome degradation. Osteoblast conditional Otub1 knockout mice showed a bone loss, suggesting an important role of Fgfr2 in maintaining bone homeostasis ( Zhu et al, 2023b ).…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid information of HOIP, HOIL-1, SHARPIN, SMURF1, SMADs and related mutants were described in the previous studies 2 , 62 . Potential HOIP-interacting proteins, such as HK1, HK2 were cloned into the 3 × Flag-CMV14 vectors.…”
Section: Methodsmentioning
confidence: 99%
“…Femurs from 8-week-old mice were fixed in 4% PFA for 48 h and then stored in 75% ethanol at 4 °C for Micro CT analysis according the previous study 62 and the femurs were subjected to a three-point bending test by using a universal testing device (CellScale Biomaterials Testing, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggest that this is a result of an increased proliferation of parenchymal and mesenchymal cells which leads to a reduction in saccular air space, potentially elevating lung tissue resistant to mechanical stretching ( Ruiz-Serrano et al, 2021 ). Furthermore, it has also been demonstrated that OTUB1 deficient mice exhibit a significant delay in bone formation in the skull and limbs at embryonic day E16.5 when compared to control littermates, which becomes even more pronounced at E18.5 ( Zhu et al, 2023 ). In adult mice, deletion of Otub1 also induces proliferation in lung tissue and alveolar hyperventilation.…”
Section: Non-catalytic Functions Of Dubs and Ubl Proteasesmentioning
confidence: 99%